Pengaruh Likuiditas, Leverage, dan Aktivitas terhadap Rentabilitas pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia Periode 2011-2017 - Angel Garcia; Yuni Siawira; Lisa Octavia Liunardi; Calvin Adrian; Silvana Silvana; Mahmuddin Syah Lubis (Politeknik Ganesha Medan, 2019)
The objective of the study is to test and analyze the effect of liquidity, leverage, and activity on profitability in otomotive companies listed on the Indonesia Stock Exchange in the period of 2011-2017. The research is used a quantitive research approach. This type of research was quantitive descriptive. While the nature of research is explanatory. The research populations were otomotive companies listed in the Indonesia Stock Exchange in 2011-2017 consisting of 13 companies. The research samples were 6 companies. The result of the research stated that liquidity affected the profitability in otomotive companies in the Indonesia Stock Exchange in 2011-2017. Leverage affected the profitability in otomotive companies in the Indonesia Stock Exchange in 2011-2017. Activity affected the rentability in otomotive companies in the Indonesia Stock Exchange in 2011-2017. Simultaneously, liquidity, leverage, and activity have an effect on profitability in otomotive companies in the Indonesia Stock Exchange in 2011-2017 with the coefficient of determination is 30%.